My Child's thoughts frighten me: Maladaptive effects associated with parents' interpretation and management of children's intrusive thoughts. (December 2018) - Berman, Noah Chase; Wilver, Natalie L.; Wilhelm, Sabine
Abstract: Background and objectives: Environmental factors explain substantial variance in youth's obsessive-compulsive symptoms (OCS) and much of this research has focused upon overt parenting behaviors (e.g., accommodation). No work, however, has examined how parents' internal processes (e.g., perception of children's intrusions) influence youth's OCS. Based upon the cognitive theory of obsessions, we propose that parents' misappraisal of children's intrusions as threatening will be positively associated with (a) the number of maladaptive intrusion management strategies recommended by the parent, as well as (b) children's obsessive beliefs, (c) interpretation biases, and (d) OCS severity. Methods: Twenty-seven children ( M  = 12.81; SD  = 3.43) and the parent most involved in childcare completed diagnostic interviews and self-report questionnaires. In the laboratory, we induced obsessional anxiety in youth through a standardized in vivo paradigm (e.g., think about a personalized harm-related negative event occurring). Parents rated how they interpreted their children's unwanted thought and the intrusion management strategies they would recommend. Results: Parents who interpreted their children's intrusions as threatening recommended more maladaptive intrusion management strategies and their misappraisal positively and significantly correlated with the severity of children's obsessive beliefs, interpretation biases, and OCS, even after controlling for co-occurring internalizing symptoms. Limitations: Small sample and cross-sectional design precludes causal conclusions. Conclusions: Parents' misinterpretation of children's intrusions may operate as a mechanism by which OCS are generationally transmitted. Results can inform OC prevention programs that target parents' cognitive biases in their own psychotherapy. Highlights: We evaluated how parents' interpret and manage children's intrusions. Twenty-seven children and their primary parent participated in laboratory tasks. Parents' misinterpretation of children's intrusions predicted greater OC features in youth. Parents' misinterpretation may operate as a mechanism of generational transmission. Results inform OC prevention programs that target parents' cognitive biases.